SYNTHESIS, CHARACTERIZATION AND EVALUATION OF THE IN VITRO ANTITUBERCULOSIS ACTIVITY OF METAL COMPLEXES OF Fe(II) AND Co(II) WITH ISONIACIDE-PYRAZINAMIDE HYBRID - Valderrama Negrón, Ana Cecilia (2025)
Tuberculosis is the seventh cause of death in the world. One third of the world's population is infected with tuberculosis disease caused by Mycobacterium tuberculosis, which has developed resistance mechanisms to various first- and second-line drugs that have proven extremely difficult to treat.This work presents the synthesis of Fe(II) and Co(II) metal complexes with the hybrid of two first-line antituberculosis drugs: isoniazid (INH) and pyrazinamide (PZA), still unknown in the scientific literature, with the purpose of enhancing the anti-tuberculosis activity of both drugs.Experimentally, obtained to then obtain the Fe(II) and Co(II) complexes, and determined their antituberculous activity.The characterization of the metal complexes was carried out by elemental analysis, infrared spectroscopy (FT-IR), Raman spectroscopy, UV-Vis spectroscopy, conductivity and thermogravimetric analysis (TGA), showing that the desired complexes.Biological activity assays were carried out using the TEMA Susceptibility Method on pyrazinamide and isoniazid metallocomplexes and their precursor salts; where the cobalt complex and the hybrid present antituberculous activity.